Population, Temperature and Feeding Rate Effects on Individual Feed Efficiency in European Sea Bass (Dicentrarchus labrax) - Rodde, Charles; Vandeputte, Marc; Allal, François; Besson, Mathieu; Clota, Frédéric; Vergnet, Alain; Benzie, John A. H.; de Verdal, Hugues (Frontiers in Marine Science, 2020)
Using breeding programs to improve feed efficiency, the ratio between fish body weight gain (BWG) and feed intake (FI), could increase aquaculture sustainability through reduced feed costs and environmental impact. To this end, individual phenotypic information is required. Individual FI can be measured by isolating each fish. Under these conditions, restricting the feeding rate has proved relevant to improve feed efficiency indirectly by selecting faster-growing animals. Moreover, a restricted feeding rate reduces the work load of collecting uneaten pellets after each meal. The approach assumes the most efficient fish at high and low feeding rates are the same, but this assumption remains untested. In European sea bass (Dicentrarchus labrax), feed efficiency is likely to be impacted also by population, temperature, and their interaction, as already demonstrated for growth in this species. To investigate these issues, 200 European sea bass from three wild populations, Atlantic (AT), West Mediterranean (WM) and East Mediterranean (EM), were reared individually at two temperatures, 18°C and 24°C. Their BWG and FI were measured at six different feeding rates, from ad libitum (100% ADL) down to fasting. A trade-off between performance at 100% ADL and at fasting was observed: more efficient fish at 100% ADL showed a stronger decrease in BWG (standardized to metabolic weight) when the feeding rate was progressively lowered and lost more weight at fasting. The most efficient fish were not the same depending on the feeding rate, suggesting the feeding rate used to phenotype fish in selective breeding programs must be the same as that used in commercial practices. The slope in the linear relationship between BWG and FI (both standardized to metabolic weight) was similar among populations and temperatures. However, EM fish had a higher intercept than others, suggesting this population grew more and thus was more efficient for an equal feeding rate. Similarly, fish reared at 18°C were more efficient for an equal feeding rate. When feed efficiency was studied in fish fed at 100% ADL, the temperature effect disappeared but the population effect remained. This highlights the complex interplay between population, temperature and feeding rate when evaluating individual feed efficiency.